Design and enantioselective synthesis of chiral pyranone fused indole derivatives with antibacterial activities against Xanthomonas oryzae pv oryzae for protection of rice - Teng, Kunpeng (2024)
A new class of chiral pyranone fused indole derivatives were prepared by means of N-heterocyclic carbene (NHC) organocatalysis and demonstrated notable antibacterial activity against Xanthomonas oryzae pv oryzae (Xoo). Bioassays showed that compounds (3S,4R)-5b, (3S,4R)-5d, and (3S,4R)-5l exhibited promising in vitro efficacy against Xoo, with EC50 values of 9.05, 9.71, and 5.84 mg/L, respectively, which were superior to that of the positive controls with commercial antibacterial agents, bismerthiazol (BT, EC50 = 27.8 mg/L) and thiodiazole copper (TC, EC50 = 70.1 mg/L). Furthermore, single enantiomer (3S,4R)-5l was identified as an optimal structure displaying 55.3% and 52.0% curative and protective activities against Xoo in vivo tests at a concentration of 200 mg/L, which slightly surpassed the positive control with TC (curative and protective activities of 47.2% and 48.8%, respectively). Mechanistic studies through molecular docking analysis revealed preliminary insights into the distinct anti-Xoo activity of the two single enantiomers (3S,4R)-5l and (3R,4S)-5l, wherein the (3S,4R)-configured stereoisomer could form a more stable interaction with XooDHPS (dihydropteroate synthase). These findings underscore the significant anti-Xoo potential of these chiral pyranone fused indole derivatives, and shall inspire further exploration as promising lead structures for a novel class of bactericides to combat bacterial infections and other plant diseases.